Pelatihan Kepemimpinan Berbasis Nilai-Nilai Islam pada Siswa SMA LPP UMI Makassar - Muhammad Ashoer; Muhammad Fadhil; Jafar Basalamah; Muh. Reza Ramdhani (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: The increase in issues among high school students tends to form their character (unproductively) negatively, and a lack of understanding of religion and leadership is suspected to be contributing. In response to this phenomenon, this program aimed to deliver a leadership development program based on Islamic values to the management of LPP UMI Makassar’s OSIS board. Research Methodology: This internal community service method combines lecture, discussion, and evaluation approaches to achieve the best results. The evaluation technique is collected through questionnaires covering elements pertaining to Islamic leadership based on Nabi Muhammad SAW. This questionnaire was then issued to ascertain their level of comprehension of the material presented. This program attracted 27 students, representing 81.8 percent of the total student council board of SMA LPP UMI, Makassar. Results: The program’s findings indicated that participants better understood the concepts and attributes of leadership in the Islamic paradigm. In addition, the results also showed that the dimension of Sidiq’s character (honesty) has the highest average score (4.48), meaning that the students of LPP UMI Makassar consider honesty as the most important thing that leaders must have in the concept of Islam. Conclusion: This outcome is designed to instill an Islamic leadership attitude in SMA UMI’s student council students, enabling them to contribute positively to Indonesia in the future.